Electrodynamics:an introduction including quantum effects - Muller-Kirsten, Harald J W (New Jersey: World Scientific, 2004)
An extensive text on electrodynamics with detailed explanations and calculations. One hundred worked examples have been incorporated, making the book suitable also for self-instruction. Apart from all traditional topics of Maxwell theory, the book includes the special theory of relativity and the Lagrangian formalism and applications; the text also contains introductions to quantum effects related to electrodynamics, such as the Aharonov-Bohm and the Casimir effects. Numerous modern applications in diverse directions are treated in the examples.
Appendix A-C, 495-514p.; Bibliography 515-516p.; Index 517-522p.
Keywords: Physics; Electrodynamics